(untitled) (Ludi Litterarri, 2026)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on students’ learning outcomes in the IPAS subject for fourth-grade students at SD Negeri 091262 Karang Sari. This research is motivated by the low student learning outcomes in the IPAS subject, caused by the use of less varied learning models that remain teacher-centered. The research method used is a quantitative approach with an experimental research design. The research design applied is a one-group pretest-posttest design. The population consists of all fourth-grade students at SD Negeri 091262 Karang Sari, with a sample of 25 students. Data collection was conducted through multiple-choice tests that had been tested for validity and reliability. The results indicate that there is a significant difference in learning outcomes between the pretest and posttest. This is proven by hypothesis testing using the paired samples t-test, where the calculated t-value (32.047) is greater than the t-table value (2.067), so Ha is accepted and Ho is rejected. It can be concluded that the Problem-Based Learning (PBL) model has a significant effect on students’ learning outcomes in the IPAS subject for fourth-grade students at SD Negeri 091262 Karang Sari.